Characteristics of Storage of Grapes in Normal Atmospheric Environment (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
In the article, the influence of agrobiological and technological characteristics of storage of different grape varieties grown in Fergana region in refrigerated warehouses on shelf life is studied. 72,861 thousand tons were grown in Greece, 51,128 thousand tons in Chile, 37,049 thousand tons in South Africa. Among the developed countries of the world, in the first place in terms of grape cultivation, "Spain is 966 thousand hectares, with a yield of 56.9 s/ha, in second place is China with 855 thousand hectares, with a yield of 154 s/ha, and in Italy 782 thousand hectares. , gross yield 102.3 s/ha, followed by Turkey with 436 thousand hectares, gross yield 96.3 s/ha and USA 408 thousand hectare, gross yield 163.7 s/ha" requires the implementation of innovative technologies in the storage of cultivated grapes. In this regard, the use of modern technologies in the cultivation and storage of grapes is one of the urgent issues.